UNICORNS IN ONCOLOGY: VALUE CREATION AND ALLOCATION - THIELSCHER, Christian (Journal of European Economy, 2024)
Unicorns in oncology create enormous value (over 60 billion). However, little is known about their economics. All 117 unicorns in the field of medicine and healthcare were analyzed to determine the extent to which they are oncologically significant. For the selected companies–those active in the field of oncology– location, business model, and value distribution were modeled. Twenty-two of the 117 highest-valued medical unicorns also, or predominantly, focus on oncology. With three exceptions, all are based in the USA. Their valuations range from 1.0 to 8.1 billion. By analyzing their business models further, we found eight different product/service offerings. The value added and its distribution are as follows: 60% to investors, 27% to sunk costs, 13% to management, and 1% to data providers. Oncological health tech unicorns create enormous value, but whether this value creation flows into the care system or is extracted from it is an open question. JEL: I11.